어린이급식관리지원센터, 유아교육기관과 가정을 연계한 영양교육 프로그램의 개발 및 효과에 대한 연구 - 조채영(Chae-Young Jo); 김지현(Ji-Hyeon Kim); 한진숙(Jin-Suk Han) (東아시아食生活學會誌, 2015)
The purpose of this study was to develop and evaluate a nutritional education program for preschool children in association with Center for Children's Foodservice Management, childcare facilities and home in order to provide nutritional knowledge and change food attitudes in children. The program was repeated three times using the same educational theme and consisted three steps. Step 1 involved visiting education with teaching tools by a dietician. Step 2 involved home education with a worksheet and participating in events with parents. Step 3 involved repeated education with a textbook by a preschool teacher education reports sent to the center. The subjects of this study were 3 to 5-year-old children at 89 childcare facilities located in Busanjingu. Interest in meals at childcare facilities, dietary guidance for parents of children, and dietary attitudes of children were evaluated before and after education. Number of parents interested in meals managed by childcare facilities (kitchen visiting, meals observation, progress of children's education) increased after education. Mean scores for meal awareness in parents in the form of three questions (proper food distribution, hand washing before mealtime, nutritional and hygienic satisfaction with meals) significantly (p<0.05) increased after education. Mean dietary guidance for parents' scores for all questions except table manner significantly (p<0.01) increased after education. Mean dietary attitudes for children in the form of six questions (try to eat various vegetable, eat meals without leaving, wash hands before mealtime, eat cleanly, reduce sodium intake and keep table manner) also significantly (p<0.001) increased after education. As a results, the nutritional education program applied in this study, positive influenced children's nutritional knowledge and dietary attitudes, and parents' dietary guidance of children.